2022
DOI: 10.1055/a-1906-0960
|View full text |Cite
|
Sign up to set email alerts
|

Noise and Critical Sound Levels During Non-Invasive Ventilation of a Preterm Infant in the Incubator

Abstract: Background Preterm birth and the subsequent necessary treatment in neonatal intensive care units (NICU) subjects the preterm infant to non-physiological noise exposure with potentially adverse consequences for short-and long-term development. Adjusters to improve the acoustic environment for the preterm infant need to be defined.Methods Sound pressure level measurements during routine procedures in a NICU were performed by ¼" microphones placed inside and outside the incubator. The microphones need to be suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…While there is a reduction of sound transmission from outside the incubator, less is known about the sound dynamics and sound characteristics of noises generated inside the incubator, primarily from medical devices such as those used for respiratory support (20). Reuter et al (21), further reported the incubator to be a bass booster for noises generated outside the incubator, while Kaiser et al (22), emphasizes the high frequency range produced by non-invasive ventilation within the incubator.…”
Section: Introductionmentioning
confidence: 99%
“…While there is a reduction of sound transmission from outside the incubator, less is known about the sound dynamics and sound characteristics of noises generated inside the incubator, primarily from medical devices such as those used for respiratory support (20). Reuter et al (21), further reported the incubator to be a bass booster for noises generated outside the incubator, while Kaiser et al (22), emphasizes the high frequency range produced by non-invasive ventilation within the incubator.…”
Section: Introductionmentioning
confidence: 99%